2000
DOI: 10.2105/ajph.90.2.216
|View full text |Cite
|
Sign up to set email alerts
|

A community-level HIV prevention intervention for inner-city women: results of the women and infants demonstration projects

Abstract: A B S T R A C TObjectives. This study examined the effects of a multisite communitylevel HIV prevention intervention on women's condom-use behaviors.Methods. The theory-based behavioral intervention was implemented with low-income, primarily African American women in 4 urban communities. It was evaluated with data from pre-and postintervention cross-sectional surveys in matched intervention and comparison communities.Results. At baseline, 68% of the women had no intention of using condoms with their main partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(20 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…During the first meeting, four interventions were dropped: PROMISE, 34 Future is Ours, 46 Real AIDS Prevention Project, 47 and VOICES. 48 Reasons for these exclusions included being too general or having elements that were difficult to adapt, 34 being too long, 46 being too difficult to sustain and including male partners, 47 and issues regarding reliability of intervention materials and depth of skill acquisition. 48 Two interventions were retained: RESPECT 49 and Sister-to-Sister (STS).…”
Section: Resultsmentioning
confidence: 99%
“…During the first meeting, four interventions were dropped: PROMISE, 34 Future is Ours, 46 Real AIDS Prevention Project, 47 and VOICES. 48 Reasons for these exclusions included being too general or having elements that were difficult to adapt, 34 being too long, 46 being too difficult to sustain and including male partners, 47 and issues regarding reliability of intervention materials and depth of skill acquisition. 48 Two interventions were retained: RESPECT 49 and Sister-to-Sister (STS).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hope for the future, homeless women need partner negotiation self-efficacy skills to reduce risky sexual activity. Women may prefer that these interventions be delivered by those perceived to be most like them (e.g., women who have “been through it” and/or women who are HIV positive), such as Community PROMISE (CDC AIDS Community Demonstration Projects Research Group, 1999), Real AIDS Prevention Project Lauby, Smith, Stark, Person, & Adams (2000), and Sistas Informing Sistas about Topics on AIDS (DiClemente & Wingood, 1995). …”
Section: Discussionmentioning
confidence: 99%
“…First, we found that people who were involved in a relationship with someone used condoms less often than those who were not similarly involved. Other researchers as well have reported that condom use tends to be less consistent among persons who are “involved” than it is among those who are not (Lauby et al 2000; Thomas et al 1999). Usually, this practice of not using condoms on a consistent basis is attributed to feelings of health-related safety and trust among persons in relationships, and to a lesser extent to the desire to conceive a child among some couples.…”
Section: Discussionmentioning
confidence: 99%